Zwitterionic liquid-based solid electrolyte membrane as well as preparation method and application thereof

By using 3-(1-vinyl-3-imidazolyl)propanesulfonate to prepare zwitterionic liquid-based solid electrolyte membranes, the problem of low conductivity in zinc-empty batteries is solved, and high moisture content and fast ion migration channels are achieved , improving the performance of zinc-air batteries and the stability of flexible energy storage devices.

CN119192475AActive Publication Date: 2024-12-27ZHEJIANG NORMAL UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411612327.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-27
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing solid electrolyte membrane has low conductivity in zinc-empty batteries and cannot meet the high performance needs of flexible electronic devices.

Method used

Using 3-(1-vinyl-3-imidazolyl)propanesulfonate as raw material, a zwitterionic liquid-based solid electrolyte membrane was prepared through photocatalytic polymerization and ion exchange technology to form a high moisture content and rapid ion migration. channel membrane.

Benefits of technology

It significantly improves the conductivity and mechanical properties, can maintain the stability of the battery under complex usage conditions, and improves the performance of zinc-air batteries and the development of flexible energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192475A_ABST
    Figure CN119192475A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemistry, and particularly relates to a zwitterionic liquid-based solid electrolyte membrane and a preparation method and application thereof.The preparation method comprises the following steps that 3-(1-vinyl-3-imidazolyl) propanesulfonate powder and N, N '-methylene bisacrylamide serve as cross-linking agents, methyl alcohol and water are added, and a 3-(1-vinyl-3-imidazolyl) propanesulfonate solution is obtained; then adding a photoinitiator, and carrying out photocatalytic polymerization reaction under the irradiation of ultraviolet light to obtain the 3-(1-vinyl-3-imidazolyl) propanesulfonate solid film. The 3-(1-vinyl-3-imidazolyl) propanesulfonate solid-state membrane is soaked in an alkaline solution for ion exchange to obtain the zwitterionic liquid-based solid-state electrolyte membrane, and compared with a unisexual ionic liquid membrane, the 3-(1-vinyl-3-imidazolyl) propanesulfonate solid-state membrane has higher conductivity, so that the problem of low conductivity of an artificial polymer electrolyte membrane is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry, and in particular relates to a zwitterionic liquid-based solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Flexible electronic devices are experiencing a period of rapid development, and traditional rigid batteries can no longer meet the increasingly diverse usage environments. Among flexible energy storage devices, flexible zinc-air batteries have become a hot topic of research due to their excellent safety, low cost, and high theoretical energy density.

[0003] Flexible zinc-air batteries consist of a zinc anode, an air cathode, and a conductive OH - The solid electrolyte membrane overcomes the problems of alkaline electrolyte leakage and solution evaporation and drying, and gives the battery a certain plasticity. Therefore, the development of solid electrolytes with high ion conductivity and water retention can promote the development of flexible zinc-air batteries.

[0004] The existing preparation method usually uses artificial polymer materials such as polyvinyl alcohol, polyacrylic acid and polyacrylamide as raw materials to prepare solid electrolyte membranes. However, the electrolyte membrane prepared by this method stores electrolytes due to its network structure. - The conduction mainly depends on the adsorption of electrolyte by gel, resulting in relatively low conductivity. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a zwitterionic liquid-based solid electrolyte membrane and a preparation method and application thereof. A zwitterionic liquid solid electrolyte membrane is prepared using 3-(1-vinyl-3-imidazolyl)propanesulfonate as a raw material. The solid electrolyte membrane formed by 3-(1-vinyl-3-imidazolyl)propanesulfonate is an alkaline anion exchange membrane. There are positive and negative charges in its structure that can be tightly combined with water molecules, ensuring a high water content. The fast ion migration channel ensures high conductivity. The polymerization between monomers promotes the mechanical properties of the electrolyte. It is applied to batteries and can withstand complex and changeable usage conditions.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a zwitterionic liquid-based solid electrolyte membrane comprises the following steps: 3-(1-vinyl-3-imidazolyl)propane sulfonate powder is used as a monomer and N,N'-methylenebisacrylamide is used as a crosslinking agent. A mixed solvent of methanol and water is added to the monomer and the crosslinking agent to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solution. A photoinitiator is added to the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution. Under ultraviolet light irradiation, a photocatalytic polymerization reaction occurs to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solid film.

[0007] The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane is immersed in an alkaline solution for ion exchange to obtain a zwitterionic liquid-based solid electrolyte membrane.

[0008] The invention uses 3-(1-vinyl-3-imidazolyl) propane sulfonate powder as a monomer and N,N'-methylenebisacrylamide as a crosslinking agent, adds a mixed solvent of methanol and water to obtain a 3-(1-vinyl-3-imidazolyl) propane sulfonate solution, adds a photoinitiator to the 3-(1-vinyl-3-imidazolyl) propane sulfonate solution, and generates a photocatalytic polymerization reaction under ultraviolet light to obtain a 3-(1-vinyl-3-imidazolyl) propane sulfonate solid film. The vinyl groups at the ends of 3-(1-vinyl-3-imidazolyl)propanesulfonate are polymerized into chains, which are cross-linked with N,N'-methylenebisacrylamide to form a network structure under the irradiation of ultraviolet light, in which the molecular chains are transformed from disorder to order, forming a solid propanesulfonate electrolyte membrane; the 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane is immersed in an alkaline solution for ion exchange, in which the anionic and cationic groups of the zwitterionic liquid itself construct channels for the transmission of ions, thereby obtaining a zwitterionic liquid-based solid electrolyte membrane.

[0009] In a preferred embodiment of the present invention, the mass ratio of 3-(1-vinyl-3-imidazolyl)propanesulfonate powder to N,N'-methylenebisacrylamide is 20-30:1.

[0010] In a preferred embodiment of the present invention, the mass fraction of 3-(1-vinyl-3-imidazolyl)propanesulfonate powder in the mixed solvent of methanol and water is 20% to 60%.

[0011] In a preferred embodiment of the present invention, the photoinitiator is one of 2-hydroxy-2-methyl-1-phenylpropanone, benzoin ethyl ether, 2-hydroxy-2-methylpropiophenone, and azobisisobutyramidine hydrochloride, and the mass fraction of the photoinitiator in the 3-(1-vinyl-3-imidazolyl)propanesulfonate solution is 2% to 5%.

[0012] In a preferred embodiment of the present invention, in the mixed solvent of methanol and water, the mass ratio of methanol to water is 1-5:1.

[0013] In a preferred embodiment of the present invention, the alkaline solution is a mixed solution of 1-6 M KOH and 0.1-0.2 M Zn(Ac)2, and the ion exchange time is 24 h to 72 h.

[0014] In a preferred embodiment of the present invention, the method for preparing the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder comprises the following steps: 1-vinylimidazole is dissolved in acetone to obtain a first solution, 1,3-propane sultone is dissolved in acetone to obtain a second solution, the second solution is mixed with the first solution under a nitrogen environment, and stirred at room temperature to obtain a mixed solution, and the mixed solution is post-treated to obtain (3-(1-vinyl-3-imidazolyl)propanesulfonate) powder.

[0015] The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 7, characterized in that the molar ratio of 1-vinylimidazole to 1,3-propane sultone is 1 to 5:1, the amount ratio of 1-vinylimidazole to acetone is 0.1 mol:60 mL to 120 mL, and the amount ratio of 1,3-propane sultone to acetone is 0.1 mol:40 mL to 100 mL.

[0016] .

[0017] Another object of the present invention is to provide a zwitterionic liquid-based solid electrolyte membrane prepared by any of the preparation methods described above.

[0018] The third object of the present invention is to provide an application of the above-mentioned zwitterionic liquid-based solid electrolyte membrane in zinc-air batteries and zinc-ion batteries.

[0019] Each structural unit of the zwitterionic liquid carries a pair of oppositely charged charges, which can form a zwitterionic solid gel after cross-linking. Due to the unique structure of anions and cations, it has special properties. First, although the zwitterions are electrically neutral, the positive and negative charges coexisting in their structure are easy to combine with water molecules, solvate, and form a water layer on the surface, showing super hydrophilicity. Secondly, there is a strong electrostatic interaction between the zwitterionic liquids, which is caused by the charged groups and anti-free ions of the structural units. The existence of strong electrostatic interactions forms non-interfering ion transmission channels in the zwitterionic liquid solid electrolyte membrane. Benefiting from the various advantages of zwitterionic liquids, the present invention uses a chemical substance with a unique structure, 3-(1-vinyl-3-imidazolyl) propane sulfonate, as a raw material to prepare a zwitterionic liquid solid electrolyte membrane. The solid electrolyte membrane formed by 3-(1-vinyl-3-imidazolyl)propanesulfonate is an alkaline anion exchange membrane. In its structure, there are positive and negative charges that can tightly bind to water molecules, ensuring a high water content; the fast ion migration channel ensures high conductivity; the polymerization between monomers promotes the mechanical properties of the electrolyte, and it is used in batteries and can withstand complex and changeable usage conditions.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses 3-(1-vinyl-3-imidazolyl) propane sulfonate powder as a monomer and N,N'-methylenebisacrylamide as a crosslinking agent, adds a mixed solvent of methanol and water to obtain a 3-(1-vinyl-3-imidazolyl) propane sulfonate solution, adds a photoinitiator to the 3-(1-vinyl-3-imidazolyl) propane sulfonate solution, and generates a photocatalytic polymerization reaction under ultraviolet light to obtain a 3-(1-vinyl-3-imidazolyl) propane sulfonate solid film. The vinyl groups at the end of 3-(1-vinyl-3-imidazolyl)propanesulfonate are polymerized into chains, and cross-linked with N,N'-methylenebisacrylamide to form a network structure under the irradiation of ultraviolet light, wherein the molecular chains are transformed from disorder to order, forming a solid propanesulfonate electrolyte membrane; the 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane is immersed in an alkaline solution for ion exchange, wherein the anion and cation groups of the zwitterionic liquid itself construct a channel for the transmission of ions, and a zwitterionic liquid-based solid electrolyte membrane is obtained. The present invention uses 3-(1-vinyl-3-imidazolyl)propanesulfonate, a chemical substance with a unique structure, as a raw material to prepare a zwitterionic liquid solid electrolyte membrane. The solid electrolyte membrane formed by 3-(1-vinyl-3-imidazolyl)propanesulfonate is an alkaline anion exchange membrane, and there are positive and negative charges in its structure that can be tightly combined with water molecules, ensuring a high water content, and a fast ion migration channel to ensure high conductivity. The polymerization between monomers promotes the mechanical properties of the electrolyte, and it is applied to batteries and can withstand complex and changeable use conditions.

[0021] 2. The present invention highlights the structural advantages and excellent performance of 3-(1-vinyl-3-imidazolyl) propane sulfonate-based electrolytes by comparing them with 1-vinyl-3-butylimidazolium bromide monoionic liquid solid electrolytes. Compared with monoionic liquid membranes, 3-(1-vinyl-3-imidazolyl) propane sulfonate membranes have higher conductivity, which improves the problem of low conductivity of artificial polymer electrolyte membranes. 3-(1-vinyl-3-imidazolyl) propane sulfonate is applied to zinc-air batteries, which can make electronic devices operate under bending conditions, and the voltage remains stable after multiple bending. The structural design and application of 3-(1-vinyl-3-imidazolyl) propane sulfonate contribute to the development of zinc-air batteries. With its unique structure, it can also be applied to other batteries, further promoting the development and progress of energy storage devices.

[0022] 3. The present invention designs the structure of zwitterionic liquids, and utilizes its unique structural advantages to prepare electrolyte membranes with high hydrophilicity and high ionic conductivity. By designing the material structure, 3-(1-vinyl-3-imidazolyl) propanesulfonate powder is prepared; compared with the monoionic liquid 1-vinyl-3-butylimidazolium bromide electrolyte, the prepared zwitterionic liquid 3-(1-vinyl-3-imidazolyl) propanesulfonate membrane has higher conductivity; by controlling the concentration of 3-(1-vinyl-3-imidazolyl) propanesulfonate in the membrane, the electrolyte membrane achieves higher conductivity under high concentration and high temperature conditions; by controlling the length of photocatalytic time, a flexible electrolyte membrane is prepared, realizing the bending application of zinc-air batteries. The above inventions and designs promote the development of flexible zinc-air batteries and provide support for the application of zwitterionic liquid electrolyte membranes in energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The invention discloses a reaction mechanism and process of film formation by cross-linking zwitterionic liquid 3-(1-vinyl-3-imidazolyl)propanesulfonate with N,N'-methylenebisacrylamide.

[0024] Figure 2 The structural formulas of 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide of the present invention are compared.

[0025] Figure 3 The FTIR spectra of 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide of the present invention are shown in FIG.

[0026] Figure 4 The XPS spectra of 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide of the present invention are shown in FIG.

[0027] Figure 5 The EDX spectrum of 3-(1-vinyl-3-imidazolyl)propanesulfonate of the present invention is shown in FIG.

[0028] Figure 6 The EDX spectrum of 1-vinyl-3-butyl imidazole bromide of the present invention is shown in FIG.

[0029] Figure 7 The conductivity-temperature relationship diagram of different concentrations of 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide.

[0030] Figure 8The invention discloses a zinc-air battery assembled with a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane, wherein 1 is an air cathode, 2 is a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane, and 3 is a zinc anode.

[0031] Fig. 9 It is the open circuit voltage of the battery assembled with 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide electrolyte of the present invention.

[0032] Fig.10 The battery assembled with 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide electrolyte of the present invention has a high conductivity at 1 mA / cm 2 Comparison of discharge time under constant current.

[0033] Fig.11 The polarization curves of 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide ZAB of the present invention are shown in FIG.

[0034] Fig.12 The power density curves of 3-(1-vinyl-3-imidazolyl)propanesulfonate and 1-vinyl-3-butylimidazolium bromide-based ZAB of the present invention are shown in FIG.

[0035] Fig.13 The invention relates to the voltage stability measurement of the 3-(1-vinyl-3-imidazolyl)propanesulfonate-based electrolyte membrane of the present invention when it is applied to a flexible zinc-air battery and bent at different angles.

[0036] Fig.14 This is an assembly diagram of the 3-(1-vinyl-3-imidazolyl)propanesulfonate-based zinc-air battery of the present invention.

[0037] Fig.15 This is a diagram showing the practical application of the 3-(1-vinyl-3-imidazolyl)propanesulfonate-based zinc-air battery of the present invention. DETAILED DESCRIPTION

[0038] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0040] Example 1 A method for preparing a zwitterionic liquid-based solid electrolyte membrane comprises the following steps: (1) 0.1 mol of 1-vinylimidazole was dissolved in 60 mL of acetone to obtain solution A, and then 0.1 mol of 1,3-propanesultone was dissolved in 40 mL of acetone to obtain solution B. Solution B was added dropwise to solution A under a nitrogen environment at 0°C. After three days of stirring at room temperature, the obtained mixed solution was filtered to obtain a solid powder, which was washed three times with acetone and dried under vacuum at room temperature to obtain 3-(1-vinyl-3-imidazolyl)propanesulfonate powder.

[0041] (2) 0.2 g of the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder prepared in step (1) and 0.01 g of N,N'-methylenebisacrylamide as a cross-linking agent were placed in a test tube, and 103 μL of methanol and 40 μL of water were added dropwise thereto to dissolve the solid, thereby preparing a 3-(1-vinyl-3-imidazolyl)propanesulfonate solution with a mass concentration of 60%.

[0042] (3) Add 2% by mass of a photoinitiator, 2-hydroxy-2-methyl-1-phenylpropanone, to the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution, shake and stir evenly, place a silicone gasket with a 16 mm*16 mm round hole on a light-transmitting glass plate, drop the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution into the round hole, cover the plate with a layer of glass, irradiate with ultraviolet light for 10 min, and irradiate the reverse side for 5 min to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solid film.

[0043] (4) The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane was immersed in a solution containing 6 M KOH and 0.2 M Zn(AC)2 for 24 hours to perform ion exchange, thereby obtaining a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane.

[0044] Example 2 A method for preparing a zwitterionic liquid-based solid electrolyte membrane comprises the following steps: (1) 0.1 mol of 1-vinylimidazole was dissolved in 60 mL of acetone to obtain solution A, and then 0.1 mol of 1,3-propanesultone was dissolved in 40 mL of acetone to obtain solution B. Solution B was added dropwise to solution A under a nitrogen environment at 0°C. After three days of stirring at room temperature, the obtained mixed solution was filtered to obtain a solid powder, which was washed three times with acetone and dried under vacuum at room temperature to obtain 3-(1-vinyl-3-imidazolyl)propanesulfonate powder.

[0045] (2) 0.2 g of the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder prepared in step (1) and 0.01 g of N,N'-methylenebisacrylamide as a cross-linking agent were placed in a test tube, and 166 μL of methanol and 67 μL of water were added dropwise thereto to dissolve the solid, thereby preparing a 3-(1-vinyl-3-imidazolyl)propanesulfonate solution with a mass concentration of 50%.

[0046] (3) Add 2% by mass of a photoinitiator, 2-hydroxy-2-methyl-1-phenylpropanone, to the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution, shake and stir evenly, place a silicone gasket with a 16 mm*16 mm round hole on a light-transmitting glass plate, drop the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution into the round hole, cover the plate with a layer of glass, irradiate with ultraviolet light for 10 min, and irradiate the reverse side for 5 min to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solid film.

[0047] (4) The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane was immersed in a solution containing 6 M KOH and 0.2 M Zn(AC)2 for 24 hours to perform ion exchange, thereby obtaining a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane.

[0048] Example 3 A method for preparing a zwitterionic liquid-based solid electrolyte membrane comprises the following steps: (1) 0.1 mol of 1-vinylimidazole was dissolved in 60 mL of acetone to obtain solution A, and then 0.1 mol of 1,3-propanesultone was dissolved in 40 mL of acetone to obtain solution B. Solution B was added dropwise to solution A under a nitrogen environment at 0°C. After three days of stirring at room temperature, the obtained mixed solution was filtered to obtain a solid powder, which was washed three times with acetone and dried under vacuum at room temperature to obtain 3-(1-vinyl-3-imidazolyl)propanesulfonate powder.

[0049] (2) 0.2 g of the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder prepared in step (1) and 0.01 g of N,N'-methylenebisacrylamide as a cross-linking agent were placed in a test tube, and 250 μL of methanol and 100 μL of water were added dropwise thereto to dissolve the solid, thereby preparing a 3-(1-vinyl-3-imidazolyl)propanesulfonate solution with a mass concentration of 40%.

[0050] (3) Add 2% by mass of a photoinitiator, 2-hydroxy-2-methyl-1-phenylpropanone, to the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution, shake and stir evenly, place a silicone gasket with a 16 mm*16 mm round hole on a light-transmitting glass plate, drop the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution into the round hole, cover the plate with a layer of glass, irradiate with ultraviolet light for 10 min, and irradiate the reverse side for 5 min to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solid film.

[0051] (4) The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane was immersed in a solution containing 6 M KOH and 0.2 M Zn(AC)2 for 24 hours to perform ion exchange, thereby obtaining a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane.

[0052] Example 4 A method for preparing a zwitterionic liquid-based solid electrolyte membrane comprises the following steps: (1) 0.1 mol of 1-vinylimidazole was dissolved in 60 mL of acetone to obtain solution A, and then 0.1 mol of 1,3-propanesultone was dissolved in 40 mL of acetone to obtain solution B. Solution B was added dropwise to solution A under a nitrogen environment at 0°C. After three days of stirring at room temperature, the obtained mixed solution was filtered to obtain a solid powder, which was washed three times with acetone and dried under vacuum at room temperature to obtain 3-(1-vinyl-3-imidazolyl)propanesulfonate powder.

[0053] (2) 0.25 g of the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder prepared in step (1) and 0.01 g of N,N'-methylenebisacrylamide as a cross-linking agent were placed in a test tube, and 250 μL of methanol and 200 μL of water were added dropwise thereto to dissolve the solid, thereby preparing a 30% mass concentration 3-(1-vinyl-3-imidazolyl)propanesulfonate solution.

[0054] (3) Add 3% by mass of a photoinitiator, 2-hydroxy-2-methyl-1-phenylpropanone, to the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution, shake and stir evenly, place a silicone gasket with a 16 mm*16 mm round hole on a light-transmitting glass plate, drop the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution into the round hole, cover the plate with a layer of glass, irradiate with ultraviolet light for 10 min, and irradiate the reverse side for 5 min to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solid film.

[0055] (4) The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane was immersed in a solution containing 6 M KOH and 0.2 M Zn(AC)2 for 24 hours to perform ion exchange, thereby obtaining a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane.

[0056] Example 5 A method for preparing a zwitterionic liquid-based solid electrolyte membrane comprises the following steps: (1) 0.2 mol of 1-vinylimidazole was dissolved in 200 mL of acetone to obtain solution A, and then 0.1 mol of 1,3-propane sultone was dissolved in 80 mL of acetone to obtain solution B. Solution B was added dropwise to solution A under a nitrogen environment at 0°C. After three days of stirring at room temperature, the obtained mixed solution was filtered to obtain a solid powder, which was washed three times with acetone and dried in vacuum at room temperature to obtain 3-(1-vinyl-3-imidazolyl)propanesulfonate powder.

[0057] (2) 0.3 g of the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder prepared in step (1) and 0.01 g of N,N'-methylenebisacrylamide as a cross-linking agent were placed in a test tube, and 103 μL of methanol and 40 μL of water were added dropwise thereto to dissolve the solid, thereby preparing a 3-(1-vinyl-3-imidazolyl)propanesulfonate solution with a mass concentration of 60%.

[0058] (3) Add 5% by mass of a photoinitiator, 2-hydroxy-2-methyl-1-phenylpropanone, to the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution, shake and stir evenly, place a silicone gasket with a 16 mm*16 mm round hole on a light-transmitting glass plate, drop the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution into the round hole, cover the plate with a layer of glass, irradiate with ultraviolet light for 10 min, and irradiate the reverse side for 5 min to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solid film.

[0059] (4) The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane was immersed in a solution containing 6 M KOH and 0.2 M Zn(AC)2 for 48 hours for ion exchange to obtain a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane.

[0060] Example 6 A method for preparing a zwitterionic liquid-based solid electrolyte membrane comprises the following steps: (1) 0.5 mol of 1-vinylimidazole was dissolved in 300 mL of acetone to obtain solution A, and then 0.1 mol of 1,3-propane sultone was dissolved in 100 mL of acetone to obtain solution B. Solution B was added dropwise to solution A under a nitrogen environment at 0°C. After three days of stirring at room temperature, the obtained mixed solution was filtered to obtain a solid powder, which was washed three times with acetone and dried in vacuum at room temperature to obtain 3-(1-vinyl-3-imidazolyl)propanesulfonate powder.

[0061] (2) 0.2 g of the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder prepared in step (1) and 0.01 g of N,N'-methylenebisacrylamide as a cross-linking agent were placed in a test tube, and 103 μL of methanol and 40 μL of water were added dropwise thereto to dissolve the solid, thereby preparing a 3-(1-vinyl-3-imidazolyl)propanesulfonate solution with a mass concentration of 60%.

[0062] (3) Add 2% by mass of a photoinitiator, 2-hydroxy-2-methyl-1-phenylpropanone, to the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution, shake and stir evenly, place a silicone gasket with a 16 mm*16 mm round hole on a light-transmitting glass plate, drop the 3-(1-vinyl-3-imidazolyl)propane sulfonate solution into the round hole, cover the plate with a layer of glass, irradiate with ultraviolet light for 10 min, and irradiate the reverse side for 5 min to obtain a 3-(1-vinyl-3-imidazolyl)propane sulfonate solid film.

[0063] (4) The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane was immersed in a solution containing 6 M KOH and 0.2 M Zn(AC)2 and maintained for 72 hours for ion exchange to obtain a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid electrolyte membrane.

[0064] Comparative Example 1 A method for preparing a 1-vinyl-3-butylimidazolium bromide solid electrolyte membrane comprises the following steps: (1) 0.2 g of powdered 1-vinyl-3-butylimidazolium bromide and 0.01 g of N,N'-methylenebisacrylamide as a cross-linking agent were placed in a test tube, and 103 μL of methanol and 40 μL of water were added dropwise to dissolve the solid to prepare a 1-vinyl-3-butylimidazolium bromide solution with a mass concentration of 60%.

[0065] (2) Add 2% by mass of a photoinitiator, 2-hydroxy-2-methyl-1-phenylacetone, to the 1-vinyl-3-butylimidazolium bromide solution, shake and stir evenly, place a silicone gasket with a 16 mm*16 mm round hole on a light-transmitting glass plate, drop the 1-vinyl-3-butylimidazolium bromide solution into the round hole, cover the hole with a layer of glass plate, irradiate with ultraviolet light for 10 min, and irradiate the reverse side for 5 min to obtain a 1-vinyl-3-butylimidazolium bromide solid film.

[0066] (3) The 1-vinyl-3-butylimidazolium bromide solid membrane was immersed in a solution containing 6 M KOH and 0.2 M Zn(AC)2 for 72 hours to perform ion exchange, so as to obtain a 1-vinyl-3-butylimidazolium bromide solid electrolyte membrane.

[0067] Results Analysis 3-(1-vinyl-3-imidazolyl)propanesulfonate, abbreviated as VIPS, N,N'-methylenebisacrylamide, abbreviated as MBAA, 1-vinyl-3-butylimidazolium bromide, abbreviated as VBIMBr.

[0068] The process of synthesizing the VIPS membrane of the present invention is to first prepare VIPS powder, add a certain proportion of water and methanol thereto, oscillate and stir to dissolve the powder, add a photoinitiator, polymerize into a membrane under ultraviolet light, show good flexibility, and change color after ion exchange.

[0069] Figure 1 The present invention discloses a reaction mechanism and process of cross-linking film formation of zwitterionic liquid VIPS and MBAA. The vinyl groups at the ends of VIPS are polymerized into chains, which are cross-linked with MBAA to form a network structure under the irradiation of ultraviolet light. The molecular chains therein are transformed from disorder to order, forming a solid VIPS electrolyte membrane. The electrolyte is immersed in a solution containing 6 M KOH and 0.2 M Zn(Ac)2 for ion exchange, wherein the anionic and cationic groups of the zwitterionic liquid itself construct channels for the transmission of ions.

[0070] Figure 2 The structural formulas of VIPS and VBIMBr of the present invention are compared. Compared with the monoionic liquid VBIMBr, the zwitterionic liquid VIPS itself carries a pair of charges with opposite electrical properties, and therefore has an extremely high ionic group density, which makes the zwitterionic hydrogel have a stronger affinity.

[0071] Figure 3 is the FTIR spectra of VIPS and VBIMBr of the present invention, Figure 4 The XPS spectra of VIPS and VBIMBr of the present invention are compared. The functional group structures of the two are found in the spectrum of VIPS at 1031 and 1180 cm -1 Two groups of obvious absorption peaks appeared at 231.2 eV, which was attributed to the S=O stretching vibration of the sulfate group in its structure. In the XPS spectrum, VIPS was found to have a peak at 231.2 eV attributed to S 2p, which further illustrates the difference between VIPS and VBIMBr in structure.

[0072] Figure 5 is the EDX spectrum of VIPS of the present invention, Figure 6 The EDX spectrum of VBIMBr of the present invention is shown. Elemental analysis was performed on VIPS and VBIMBr electrolyte membranes, and it was found that there was obvious S element in VIPS.

[0073] Figure 7 The conductivity-temperature relationship diagram of VIPS and VBIMBr of different concentrations in the present invention is shown in the figure. The conductivity of the electrolyte membrane of 30 wt%, 40 wt%, 50 wt%, 60 wt% VIPS and 60 wt% VBIMBr was tested at different temperatures, and it was found that the conductivity is proportional to the temperature. At the same concentration, the conductivity of VIPS is better than that of VBIMBr.

[0074] Figure 8 The zinc-air battery assembled with the VIPS solid electrolyte membrane of the present invention, wherein 1 is an air cathode, 2 is a 3-(1-vinyl-3-imidazolyl) propanesulfonate solid electrolyte membrane, 3 is a zinc anode, and the reaction equation of the air cathode is: O2+2H2O+4e - →4OH - The reaction equation of zinc anode is: Zn+4OH - →ZnO+2H2O+4e - The zinc anode, VIPS solid electrolyte membrane and air cathode were assembled using a button battery mold, and the reaction equations during charging and discharging were demonstrated. The air cathode was nickel foam loaded with catalysts Pt / C and Ir / C. The zinc-air batteries with VIPS-based and VBIMBr-based electrolytes were combined using the above method, and their electrochemical properties were compared.

[0075] Fig. 9 The open circuit voltage of the battery assembled with VIPS and VBIMBr electrolyte of the present invention is shown in Figure 2. It is found that VIPS-based ZAB has a higher open circuit voltage.

[0076] Fig.10 The cell assembled with VIPS and VBIMBr electrolyte at 1 mA / cm 2 Comparison of the discharge time under constant current revealed that the VIPS-based ZAB lasted longer during the discharge process, showing the structural advantage of zwitterionic liquids.

[0077] Fig.11 The polarization curves of VIPS and VBIMBr based zinc-air batteries are shown in Figure 2. The zinc-air battery is referred to as ZAB. It is found that VIPS based ZAB exhibits significant advantages under the conditions of charge and discharge. 2 Taking the current density at as an example, the ZAB voltage of the VIPS base is 490 mV lower than that of the VBIMBr base during charging and 220 mV higher during discharging, showing excellent charge and discharge capabilities.

[0078] Fig.12 The power density curves of VIPS and VBIMBr-based zinc-air batteries show that VIPS-based ZAB has a higher power density peak, proving that when ZAB is working, the VIPS electrolyte membrane can output higher power, further proving that zwitterionic liquids help improve the battery's ability to work.

[0079] Fig.13 The voltage of VIPS-based solid electrolyte membrane applied to zinc-air batteries at different bending angles was measured, and it was found that the battery voltage could still remain stable when bent at 0°C, 90°C and 180°C.

[0080] Fig.14 This is the assembly diagram of the 3-(1-vinyl-3-imidazolyl)propanesulfonate zinc-air battery of the present invention. Fig.15 This is a diagram of the actual application of the 3-(1-vinyl-3-imidazolyl)propanesulfonate-based zinc-air battery of the present invention. It can be seen that when three batteries are connected in series, the LED bulb and the bouquet string light are successfully lit, proving that the electrolyte membrane can be applied to real life and has certain development prospects.

[0081] In summary, the present invention highlights the structural advantages and excellent performance of VIPS-based electrolytes by comparing with VBIMBr monoionic liquid solid electrolytes. Compared with monoionic liquid membranes, VIPS membranes have higher conductivity, which improves the problem of low conductivity of artificial polymer electrolyte membranes. The VIPS membrane is applied to zinc-air batteries, which can enable electronic devices to operate under bending conditions, and the voltage remains stable after multiple bending. The structural design and application of VIPS contribute to the development of zinc-air batteries. With its unique structure, it can also be applied to other batteries, further promoting the development and progress of energy storage devices.

[0082] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0083] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the protection scope of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations.

Claims

1. A method for preparing a zwitterionic liquid-based solid electrolyte membrane, characterized in that: The following steps are involved: Using 3-(1-vinyl-3-imidazolyl)propanesulfonate powder as a monomer and N,N'-methylenebisacrylamide as a crosslinking agent, adding a mixed solvent of methanol and water to the monomer and the crosslinking agent to obtain a 3-(1-vinyl-3-imidazolyl)propanesulfonate solution; Adding a photoinitiator to the 3-(1-vinyl-3-imidazolyl)propanesulfonate solution, and causing a photocatalytic polymerization reaction under ultraviolet light to obtain a 3-(1-vinyl-3-imidazolyl)propanesulfonate solid film; The 3-(1-vinyl-3-imidazolyl)propanesulfonate solid membrane is immersed in an alkaline solution for ion exchange to obtain a zwitterionic liquid-based solid electrolyte membrane.

2. The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of 3-(1-vinyl-3-imidazolyl)propanesulfonate powder to N,N'-methylenebisacrylamide is 20-30:

1.

3. The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 1, characterized in that: The mass fraction of 3-(1-vinyl-3-imidazolyl)propanesulfonate powder in a mixed solvent of methanol and water is 20% to 60%.

4. The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 1, characterized in that: The photoinitiator is one of 2-hydroxy-2-methyl-1-phenylpropanone, benzoin ethyl ether, 2-hydroxy-2-methylpropiophenone, and azobisisobutyramidine hydrochloride, and the mass fraction of the photoinitiator in the 3-(1-vinyl-3-imidazolyl)propanesulfonate solution is 2% to 5%.

5. The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 1, characterized in that: In the mixed solvent of methanol and water, the mass ratio of methanol to water is 1~5:

1.

6. The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 1, characterized in that: The alkaline solution is a mixed solution of 1-6 M KOH and 0.1-0.2 M Zn(Ac)2, and the ion exchange time is 24 h-72 h.

7. The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 1, characterized in that: The preparation method of the 3-(1-vinyl-3-imidazolyl)propanesulfonate powder comprises the following steps: 1-vinylimidazole is dissolved in acetone to obtain a first solution, 1,3-propane sultone is dissolved in acetone to obtain a second solution, the second solution is mixed with the first solution under a nitrogen environment, and stirred at room temperature to obtain a mixed solution, and the mixed solution is post-treated to obtain (3-(1-vinyl-3-imidazolyl)propanesulfonate) powder.

8. The method for preparing a zwitterionic liquid-based solid electrolyte membrane according to claim 7, characterized in that: The molar ratio of the 1-vinylimidazole to 1,3-propane sultone is 1-5:1, the dosage ratio of the 1-vinylimidazole to acetone is 0.1 mol:60 mL-120 mL, and the dosage ratio of 1,3-propane sultone to acetone is 0.1 mol:40 mL-100 mL.

9. A zwitterionic liquid-based solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the zwitterionic liquid-based solid electrolyte membrane according to claim 9 in zinc-air batteries and zinc-ion batteries.

Citation Information

Patent Citations

  • Alkaline polyelectrolyte film and preparation method thereof

    CN101362832A

  • Repairable ionic gel electrolyte and preparation method and application thereof

    CN112599863A

  • Zwitterionic hydrogel, electrolyte, secondary battery or supercapacitor, and electric device

    CN113698718A

  • Vinyl imidazole polyion liquid-based solid polymer electrolyte membrane for lithium battery and preparation method of vinyl imidazole polyion liquid-based solid polymer electrolyte membrane

    CN116315061A

  • Preparation method of gel electrolyte, gel electrolyte and lithium battery

    CN116526028A